Improved VMD-+ACO Algorithm Navigation and Positioning Technology for Robot Electric Power Inspection - Long, Yingkai; Du, Mingming; Luo, Xiaoxiao; Li, Siquan; Jiang, Xiping (International transactions on electrical energy systems, 2022)
In order to meet the navigation and positioning requirements of force inspection robot, a new technology based on improved VMD- + ACO algorithm is proposed. The main content of this technology is based on the research of improved VMD algorithm and ACO algorithm, through the comparison of VMD algorithm and improved VMD algorithm. By using ACO parameter optimization design and so on, the research means of improving VMD- + ACO algorithm navigation and positioning technology of electric inspection robot is finally established through experiments and analysis. The experiment result shows the following. The minimum iteration number of the improved ACO is 112, which is 24.32% less than that of the basic ACO. The mean value of the worst value and the optimal value of the function are equal to 0. It shows that the improved ACO has higher convergence precision and the number of iterations is significantly reduced. Conclusion. Based on the improved VMD- + ACO algorithm, it can meet the navigation and positioning requirements of electric inspection robot.